Lagenandra limbusleviterapertae, a new addition to the genus Lagenandra (Araceae) from Sri Lanka - Madola, Indrakheela; Yakandawala, Deepthi; Yakandawala, Kapila (Phytotaxa, 2023)
Lagenandra limbusleviterapertae, a new species of Lagenandra from the Hiyare Forest Reserve, Galle District is described and illustrated. The new species can be differentiated from all other described Lagenandra species on the basis of the linear limb, where the limb opens only at the base of the tail extending only about 1/5 of the length and the width of the opening remains < 5 mm. Detailed morphological characters, diagnostic comparisons, notes on habitat and ecology are presented. Based on the IUCN Red List categories and criteria, the new species is assessed as Critically Endangered under Criterion B1ab(iii, v)+B2ab(iii, v)+C2a(i).